Texture image segmentation based on estimation of density of contour elements and absorption of small regions - H. M. Alzakki; V. Yu. Tsviatkou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Texture image segmentation method based on estimation of density of contour elements and absorption of small regions, providing an increase in the accuracy in the selection of texture regions in the images to the specification of their boundaries is proposed.